Impact of Cooperative and Thrift Societies on Small Business Performance in Nigeria: Array - Ogunmuyiwa, Michael; Oluwasanya, O. P.; Aladegoroye, O. R. (The Journal of Accounting and Management, 2021)
Objectives: This study investigated the impact of participatory rate of cooperative members on small business performance in Nigeria. Prior Work: Previous studies focused more on the relationship between cooperative and thrift societies and small business performance without paying adequate attention to participatory rate of members. Approach: The study was conducted among cooperative and thrift members in Six (6) Local Government Areas in Ogun Central Senatorial District (Ifo, Ewekoro, Obafemi/Owode, Abeokuta North, Abeokuta South, and Odeda). The study adopted survey research design and a sample size of 369 was drawn from a population of 4,836 members of cooperative societies in the Six (6) Local Government Areas using judgmental sampling technique. Descriptive statistics (DS) and Ordinary Least Square (OLS) were employed to test the hypotheses formulated using 5% level of significance. Result: Result revealed that Financial Services (FIS) has significant effect on small business performance (β = 0.4131; tc = 5.7988; p < 0.05). Also, Non – Financial Services (NFIS) has significant effect on small business performance (β = 0.2708; tc = 3.2023; p < 0.05). In addition, Socio-economic Factor and Membership (SEF/MEM) has significant effect on performance of small businesses (β = 0.1817; tc = 2.6416; p < 0.05). Patronage (PAT), also has a significant effect on performance of small business (β = 0.7919; tc = 15.8113; p < 0.05). Implications: Based on these findings, the study concluded that FIS, NFIS, SEF/MEM and PAT have significant effect on the performance of small businesses in Nigeria. Thus, these elements are the critical factors influencing the performance and growth of small businesses in Nigeria. Value: Small businesses as well as SMEs in general can leverage on the dimensions of cooperative used in this study to improve performance of their enterprises.